Ticagrelor Solubility and Dissolution Rate Enhancement Using Mesoporous Silica SBA-15 - Hasanah, Uswatul; Rizky, Fattihatul; Mohd Amin, Mohd Cairul Iqbal; Zaini, Erizal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Ticagrelor is a triazolopyrimidine antiplatelet agent with poor water solubility. Ticagrelor was incorporated into mesoporous silica SBA15 in this study to evaluate its physical stability and improve its solubility and dissolution rate. TEOS was employed as a silica precursor and Pluronic P123 as a template to synthesize SBA-15. Ticagrelor was loaded into SBA-15 at a mass ratio of 1:1. Physicochemical characterization was conducted using nitrogen adsorption-desorption isotherm analysis, powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). Ticagrelor solubility and dissolution were tested using distilled water as the medium. To evaluate the physical stability, Ticagrelor-SBA-15 was stored in a climatic chamber at 75% RH and 40°C for a month and analyzed using PXRD. Physicochemical characterization indicated efficient adsorption of ticagrelor into the SBA-15 pores, resulting in an amorphous form of solid material. Meanwhile, solubility and dissolution rate testing showed respective increases of 1.33 times and 1.74 times with significant differences (p<0.05) while maintaining its physical stability after storage for one month. Based on this study, it can be concluded that the incorporation of mesoporous SBA-15 significantly enhances ticagrelor’s solubility and dissolution rate while maintaining stability.